Women's perceptions of pharmacist‐prescribed hormonal contraception. Issue 2 (21st August 2019) - Meredith, Ashley H.; Olenik, Nicole L.; Farris, Karen B.; Hudmon, Karen Suchanek
Abstract: Introduction: Unintended pregnancy is a public health issue, with young women in their late teens and early 20s at highest risk. Multiple approaches to increasing contraception access have been implemented, including adoption of statewide pharmacist prescribing legislation in multiple states. Indiana does not currently have such legislation in place. The objective of this study was to identify how women at risk for unintended pregnancy in central Indiana perceive pharmacist prescribing of contraception. Study Design: Qualitative, one‐on‐one semi‐structured interviews. Methods: Purposive, convenience sampling of eligible women 18 to 29‐years‐old who live in Indiana was used. Recruitment occurred via printed flyers placed in public locations that were not focused on health care, free classified online advertisements, and electronic flyers within Facebook social groups relevant to the study population. Interviews were conducted via telephone until thematic saturation was achieved. Participant demographics, baseline characteristics, current and past barriers to obtaining contraception, and perception of a pharmacist contraception prescribing model were collected. Interview transcripts were coded in an iterative manner with qualitative data analysis software (MAXQDA, Version 12) until consensus was achieved. Results: Fourteen women completed the study. Four primary themes emerged encompassing accessibility, communication, pharmacist attributes, and payment. Thirteen participants would personally utilize a pharmacist prescribing contraceptive service and all stated that this service would be beneficial for other women. Of those women expressing a preference (n = 7), a female pharmacist would be preferred for service delivery. Participants expressed concerns related to access by minors, skills and training of the pharmacist, and environment within the pharmacy. Conclusions: Women in Indiana desire broader access to contraception. Efforts should be made at the individual pharmacist‐provider level and statewide to explore strategies to increase access. Resources should be allocated to the creation of protocols for pharmacist prescribing within Indiana and other states.